Profile and trend analysis of diseases of the genitourinary system in the Philippines - Mangotara, Rosnia D.; Balt, Arafat M.; Demayo, Chin-Chin J.; Sambawa, Nihaya G.; Demayo, Cesar G. (International Journal of Public Health Science (IJPHS), 2024)
In the Philippines, kidney disease is acknowledged as a significant public health issue as it causes considerable suffering, negatively impacts health, and possibly death to people inflicted it, this is despite the available programs and efforts to combat these diseases. This study evaluated and analyzed six decades of data (1960-2019) from Philippine Health Statistics to provide precise and valid information regarding its mortality trend and to assess the country’s improvement in effectively dealing with these diseases. Factors such as gender, geographical location, and lifestyle were found to affect kidney disease chances. We also found out that there are age and gender disparities in the vulnerability of the people of the Philippines to kidney diseases, with elderly ages 70 and up and males recorded to be at greater risk of dying due to it. Differences in the regional outcome were also observed with Region XII having the highest mortality rate, and Region ARMM having the lowest. Urgent need to expand treatment advancements and programs for the population is needed to decrease the burden of kidney disease in the country in the following years.